2007
DOI: 10.1055/s-0039-1698304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Erosive Potential of Soft Drinks

Abstract: ObjectivesThis in vitro study evaluated the capability of different soft drinks (Coca-Cola®-C, Coca-Cola Light®-CL, Guaraná®-G, Pepsi Twist®-P and Sprite Light®-SL) to erode dental enamel, relating the percentage of superficial microhardness change (%SMHC) to concentrations of fluoride and phosphate, buffering capacity and pH of these drinks.MethodsThe soft drinks were evaluated in respect to concentration of phosphate and fluoride spectrophotometrically using Fiske, Subarrow method and by specific electrode (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
4
14
0
1
Order By: Relevance
“…According to the information from the manufacturers, citric acid, and ascorbic acid are the components of tested CE drinks. These findings are in agreement with in vitro and in situ studies that reported the potential of drinks to demineralize enamel, leading to the development of dental erosion 2627. Drinks containing higher concentrations of citric acid are more aggressive on enamel;2829 also, comparable findings in the study support this statement since the sports drinks used in this study contain citric acid or citrates.…”
Section: Discussionsupporting
confidence: 92%
“…According to the information from the manufacturers, citric acid, and ascorbic acid are the components of tested CE drinks. These findings are in agreement with in vitro and in situ studies that reported the potential of drinks to demineralize enamel, leading to the development of dental erosion 2627. Drinks containing higher concentrations of citric acid are more aggressive on enamel;2829 also, comparable findings in the study support this statement since the sports drinks used in this study contain citric acid or citrates.…”
Section: Discussionsupporting
confidence: 92%
“…Decalcification was consistently produced from both types of drinks after swishing. The results of this research are in concordance with other related researchers, that show powdered and other modified acid drinks are erosive [13,16,19]. In the research presented above, the acidity as measured by pH and buffering capacity of the drinks was all significantly lower than the critical pH 5.5.…”
Section: Figuresupporting
confidence: 92%
“…The Coca-Cola drink similarly decreased the gloss in all tested materials. The presence of different types of acids such as phosphoric acid in the composition and the pH=2.5 of that soft drink may help to explain the decrease of the brightness of the materials (20). The gloss instability of composites after immersion in acidic solutions could be explained by the softening of the organic matrix by phosphoric acid, which affected the incidence and the reflection of light, promoting the decrease of brightness (21).…”
Section: Discussionmentioning
confidence: 99%